Altruistic Experiences of Volunteers Who Participate In the Socio-Educational Activities for People with Mental Disorders - Gudinavičius, Benas; Gudonis, Vytautas (Pedagogika, 2013)
The article aims to present the results of volunteers who participate in socio-educational activities for people with mental disorders written reflections analysis based on lived experience. The aim of the research is to reveal altruistic experiences of volunteers who participate in socio - educational activities for people having mental disorders. These experiences will lead to the identification of stimulating and suppressing factors for altruism self-education and characteristics of altruism expression. 12 volunteers who participated in socio-educational activities for people with mental disorders participated in a qualitative research. Results of the research: positive experience of volunteers is linked to a successful socio-educational activities based on transformation of internal attitudes and values, adequate relationships with people having mental disorders. These factors are the baseline for a successful self-education of altruism. The main barriers for self-education of altruism are as follow: negative emotions and experiences of volunteers linked to a dominant feelings of helplessness and self-doubt, a lack of information of such kind of disability, negative evaluation and inadequate behavior of staff in relationship with people with mental disorders. The results of the research showed that there is a need to inform, consult and to support psychologically volunteers during volunteering and to educate a skills of self-reflection.